Regular Exercise Is Associated With Low Fatigue Levels and Good Functional Outcomes After COVID-19: A Prospective Observational Study. (1st May 2023) - de Avila, Leyla; Price, Jillian K.; Stepanova, Maria; Lam, Brian; Weinstein, Ali A.; Pham, Huong; Austin, Patrick; Keo, Wisna; Younossi, Zaid; Afendy, Mariam; Nader, Samir; Terra, Kathy; et al.
Abstract : Objective: The aim of the study is to identify the impact of postacute SARS-CoV-2 infection on patient outcomes. Design: This is a prospective, repeated measure, observational study of consented adults with positive SARS-CoV-2 quantitative polymerase chain reaction or antigen test more than 28 days after infection. Only data from the initial study visit are reported, including disease history, symptoms checklist, patient questionnaires, cognitive tests, social/medical histories, vitals, grip strength, and 2-min walk distance. Results: Two hundred eighteen patients were studied: 100 hospitalized (57.3 ± 15.4 yrs, 62% male, body mass index: 31.3 ± 8.0) and 118 nonhospitalized (46.2 ± 14.6 yrs, 31% male, body mass index: 29.7 ± 7.5). Post-COVID patients reported mean 1.76 symptoms; ≥15% reported fatigue, memory loss, and shortness of breath. Grip strength was 14% lower than norms ( P < 0.0001). Fatigue (Functional Assessment of Chronic Illness Therapy–Fatigue), mood (Patient Health Questionnaire), and well-being (EuroQol 5 Dimension 5 Level) scores were lower than the population norms ( P < 0.05). Hospitalized versus nonhospitalized post-COVID patients performed worse on cognitive assessments (processing speed test—Wechsler Adult Intelligence Scale–Fourth Edition Symbol Search) and reported less regular exercise (≥30 mins ≥3× per week; P < 0.05). In addition, 30% had severe fatigue (by the Functional Assessment of Chronic Illness Therapy–Fatigue); those patients reported less exercise ( P < 0.05). In multivariate models, lack of exercise was independently associated with multiple post–COVID-19 impairments. Conclusions: Low levels of exercise are an independent risk factor for post-COVID sequelae. Patients who report less exercise have low grip strength, higher levels of fatigue, memory loss, shortness of breath, depression, and poorer quality of life.